ENHANCING STUDENTS’ PROBLEM SOLVING THROUGH A FLIPPED CASED-BASED LEARNING - Diningrat, Syaiputra W.M.; Kristanto, Andi; Pradana, Hirnanda Dimas; Kholidya, Citra Fitri (Universitas Negeri Surabaya, 2024)
The implementation of flipped classroom has become popular in higher education. However, few studies have conducted on how to expand various instructional strategies into a flipped classroom practice, which is important to learning. Meanwhile, prior studies have examined the effect of case-based learning (CBL) on improving student problem solving ability. The present study thus proposed a flipped classroom combined with CBL, an extension of the classic flipped classroom model. The present study also examined the effect of flipped classroom combined with CBL on students’ problem-solving ability. To compare the effect of CBL on student problem solving in a flipped classroom, we conducted a quasi-experimental design study with three classes involving 94 students in a private university in Indonesia. Across 7 weeks, where one experimental group received Flipped classroom combined with CBL and a second experimental group received the flipped classroom model, while the control group received regular classroom activities. The results indicated that learning through the flipped classroom combined with CBL resulted in better problem-solving ability compared to the flipped classroom model and conventional method. The findings imply that a flipped classroom combined with CBL is effective in cultivating students’ problem-solving ability and need to be replicated that involve larger groups of participants